Russian food products market- new CEFTA export opportunity - Stanojević, Nataša (Industrija, 2016)
This study aims to point out the unexploited export potential of CEFTA economies to the Russian market, using both quantitative and qualitative methods. More precisely, the Russian food market is examined, because of its size, the lack of domestic supply and actual changes of trading partners due to political and security antagonisms. The competitiveness of CEFTA food production on the Russian food market was analyzed by using two classical instruments of competitiveness - coefficient of conformity (CC) and real effective exchange rate (RER).CC is applied first to the CEFTA export and Russian import of food in total, and then to the six main Russian import food products. The results indicate the highest degree of matching between Russian import and all CEFTA country export of fruits, vegetable and its processed commodities. RER is calculated to show competitiveness in terms of prices in bilateral trade, and result shows a very favorable ratio of currency, except in the case of Montenegro and Bosnia because their fixation to euro. Due to the small size of CEFTA production and non-proportional large Russian market, the interconnection, e.g. forming the value chain made of CEFTAs agriculture and food industry companies is suggested as the basis of new CEFTA export strategy.